Visitors’ satisfaction towards service and facilities in Kilim Karst Geoforest Park, Langkawi - Sapari, Mohamad Safee; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Education and Novel Technology Research Association, 2013)

(untitled)
Kilim Karst Geoforest Park (KKGP) is one of the three world heritage sites in Langkawi Island that recognized by UNESCO since 2007 . It provides nature-based attraction for instance wildlife watching, karst landscape, mangrove river, and karst caves. Last a few years, visitors arrival in KKGP has increased dramatically from 78, 145 to 273,450 between 2006 and 2012. This influx has spurred substantial increases in the demand for facilities and services. However, in terms of ecotourism destination, some visitors may not like the changes in the environment and the landscape of the park because of the development. The main objective of this study is to measure the level of visitors’ satisfaction towards quality of services and facilities at KKGP. This study uses the ECOSERV dimension that has been adapted from SERVQUAL for accessing the quality of environment, services, and facilities provided in ecotourism site. In additional, the study uses the expectation-performance analysis that has been adapted from Importance Performance Analysis (IPA) to identify the attributes in services, facilities and environment that are need priority for improvement. The result of the study found the level of visitors’ satisfaction towards quality of environment, services and facilities in the park is low. Of the 27 attributes, the study found 17 items indicates visitors are less satisfied and only 6 items really need for urgent action. The results also suggest that there are some opportunities for improving the services and facilities in KKGP especially for management, planner and service provider.